2019
DOI: 10.1017/cts.2019.385
|View full text |Cite
|
Sign up to set email alerts
|

Career orientation and perceived professional competence among clinical research coordinators

Abstract: Introduction:This study identified underlying career orientation types of clinical research coordinators (CRCs) using cluster analysis. Select career (satisfaction, engagement, and planning) and competency-related (perceived competence) information was used to identify four distinct career orientation types.Method:A web-based survey was administered to CRCs employed in one of four research institutions affiliated with a National Institutes of Health-funded Clinical and Translational Research Award (CTSA) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…A recent survey of clinical research coordinators showed lower levels of perceived competence in areas related to regulations and product development. (13) The priority placed on trainings in research compliance and research administration may be explained by the majority of responding staff self-identifying as research coordinators.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of clinical research coordinators showed lower levels of perceived competence in areas related to regulations and product development. (13) The priority placed on trainings in research compliance and research administration may be explained by the majority of responding staff self-identifying as research coordinators.…”
Section: Discussionmentioning
confidence: 99%
“…Development of skills to become a successful medical professional, including professional behavior, goal setting, establishing and maintaining self-esteem, time management, and teamwork [8]. We referenced that perceived professional competence among clinical research coordinators recommended three career constructs including career engagement (CE), career planning (CP), and career satisfaction (CS) were selected to represent career orientation [9]. Career engagement (CE) represented the degree of proactively exhibiting different career behaviors to enhance career development, is of theoretical, organizational, and personal importance [10].…”
Section: Discussionmentioning
confidence: 99%
“…According to Rojewski et al (2019), career orientation is viewed as the values articulated and plans made by an employee that have bearing on job-related choices. This implies that career orientations represent employees' preferences on specific jobrelated prospects, settings and kinds of work.…”
Section: Career Orientationmentioning
confidence: 99%